Valuing Tradable CO2 Permits for OECD Countries - Larry Karp; Xuemei Liu (Fondazione Eni Enrico Mattei (FEEM), 1999)
We estimate a structural model of OECD countries in which GDP and CO2 emissions are endogenous. We use the estimated model to simulate the price of tradable CO2 permits and the efficiency gains from trade. Our estimated prices are high, relative to previous estimates, and the efficiency gains are substantial. We also find, contrary to previous literature, that higher income is associated with reduced emissions.
Keywords: F17; Q28; Q43; 330; Tradable permits; Greenhouse gases; Carbon reductions; Environmental Kuznets curve; Emissionshandel; Handelbare Güter; Außenhandelsgewinn; Außenhandelspreis; Luftreinhaltung; Treibhausgas-Emissionen; Sozialprodukt; Theorie; OECD-Staaten